Correspondence between Vincas Krėvė-Mickevičiaus ir lithuanian diplomat in USA Povilas Žadeikis - Tamošaitis, Mindaugas (Genocidas ir rezistencija, 2009)
The publication presents the correspondence of Vincas Krėvė Mickevičius, former head of the Lithuanian puppet People’s Government and Minister of Foreign Affairs, with Povilas Žadeikis, the Lithuanian envoy to the USA, after the Second World War. The documents found in the archives of the Lithuanian Embassy in Washington reveal new details of Krėvė’s life and explain the history of his political memoirs. The documents show how Žadeikis and other Lithuanian diplomats reacted to Krėvė’s memoirs.
Keywords: Vincas Kreivė-Mickevičius; Soviet occupation; emigree; diplomacy